The Physiological Effect of Human Grooming on the Heart Rate and the Heart Rate Variability of Laboratory Non-Human Primates: A Pilot Study in Male Rhesus Monkeys - Grandi, Laura Clara; Ishida, Hiroaki (Frontiers in Veterinary Science, 2015)
Grooming is a widespread, essential and complex behavior with social and affiliative valence in the non-human primate world. Its impact at the autonomous nervous system level has been studied during allogrooming among monkeys living in a semi-naturalistic environment. For the first time, we investigated the effect of human grooming to monkey in a typical experimental situation inside laboratory. We analyzed the autonomic response of male monkeys groomed by a familiar human (experimenter), in terms of the heart rate and heart rate variability at different body parts. We considered the heart rate variability in both the time (SDNN, RMSSD and RMSSD/SDNN) and the frequency domain (HF, LF and LF/HF). For this purpose, we recorded the electrocardiogram of 2 male rhesus monkeys seated in a primate chair while the experimenter groomed their mouth, chest or arm. We demonstrated that 1) the grooming carried out by a familiar human determined a decrement of the heart rate and an increment of the heart rate variability; 2) there was a difference in relation to the groomed body part. In particular, during grooming the mouth the heart rate variability was higher than during grooming the arm and the chest. Taken together the results represent the first evidence that grooming carried out by a familiar human on experimental monkeys has the comparable positive physiological effect of allogrooming between conspecifics. Moreover since the results underlined the positive modulation of both heart rate and heart rate variability, the present study could be a starting point to improve the well-being of non-human primates in experimental condition by means of grooming by a familiar person.